Beyond sight: Comparing traditional virtual reality and immersive multi-sensory environments in stress reduction of university students - Baktash, Hanieh; Kim, Daejin; Shirazi, Amin (Frontiers in Virtual Reality, 2024)
This study aims to assess the efficacy of traditional virtual reality (VR) and Immersive Multi-sensory Environments (IME) in mitigating anxiety levels among university students. The study can address the following research questions: (1) What disparities exist in anxiety levels before and after exposure to traditional VR and IME? (2) How do anxiety levels compare between participants exposed to IME and those in a VR environment? The research adopted a two-phase approach involving participants exhibiting moderate to high-stress levels. In the second phase, participants were randomly assigned to either a VR group (solely visual stimulation) or an IME group (comprising visual, auditory, and olfactory stimuli). The State-Trait Anxiety Inventory (STAI) were utilized to assess stress and anxiety levels before and after each experiment. The findings suggest that participants' experiences in both VR and IME environments effectively contributed to reducing anxiety levels and fostering a tranquil atmosphere. Both experimental groups reported a significantly heightened sense of relaxation post-experiments. Although the disparity was not statistically significant, the IME group displayed a more pronounced reduction in stress levels compared to the VR group. In conclusion, the research underscores the significance of considering the built environment and sensory design in addressing mental health challenges among college students. Further exploration and integration of such approaches into educational settings could significantly contribute to establishing more supportive and conducive environments for student success.